Reconfiguração do espaço rural de Porto da Folha/SE : inovações socioprodutivas e ruralidades - Silva, José Natan Gonçalves da (2016)
The modernization of rural activities in family farm units consists of a recent reality in territorial configuration of Brazilian countryside and, especially, of productive sectors in Northeast’s Sertão. This process has been propelled along the last decades due to formulation and expansion of public policies oriented to the development of family farming. The reorganization of productive sectors in countryside areas is also due to the expansion of non-farming service provider activities discharged by family farmers and/or liberal workers. The complexity of the rural world is even more meaningful as we observe an interaction, in the same space, of social and productive innovations and economic, social and traditional cultural practices that reinforce the countryside social groups’ territorial identity, despite the ongoing transformations. Assuming as a base the empirical configuration of Porto da Folha/SE municipality, this study aims to analyze the reconfiguration of the rural space from the advancement of new ruralities and the resistance of traditional ruralities. The methodology applied has a qualitative approach and is founded on bibliographic research, data collection, data systematization, information, and field research using exploratory research techniques, field diary, application of interviews and iconographic recordings. The results of this research point to a reconfiguration of rural territories based on modernization of productive sectors maintained by family farmers, the advancement of non-farming activities and basic services (education, health and leisure), until then restricted to urban centers, as well as the strengthening of identities founded in the territory that contributes to a cultural legitimacy of the social groups. Therefore, the analysis about rural space dynamics must not be restricted to economic and productive relations, but also to social organization and the cultural representations of the subjects who live in countryside.